Should I stay or should I go? Approach/avoidance conflict and emotional functioning. (16th July 2018) - Wilborn, Dexter D.; Kramer, Matthew P.; Stevenson, Brittany L.; Dvorak, Robert D.
Abstract: Personality has long held a prevalent place in the pantheon of psychological research. In the last 40 years, neuropsychological models of personality have become a popular predictor of human behaviour and emotionality. With a particular focus on Gray's Reinforcement Sensitivity Theory, this study investigated the interaction of high Behavioural Activation System (BAS) and Behavioural Inhibition System (BIS) as a predictor of emotional functioning. Participants ( n = 499) recruited from the community completed an online survey composed of questions on demographic information, behavioural inhibition and activation, emotional instability and indices of depression, anxiety and mixed depression–anxiety. Consistent with our primary hypothesis, the interaction of high BAS × BIS predicted emotional instability using an observed variable path model. This was subsequently associated with depression, anxiety and mixed depression–anxiety symptoms. Future avenues for research using BIS/BAS monitoring in clinical practice and study limitations are discussed. © 2018 John Wiley & Sons, Ltd.